Language Testing And Assessment Literacy For Pre-service Efl Teachers: Between Reality And Expectations - Imane Fersaoui (The Journal of Studies in Language, Culture and Society, 2024)
The training that EFL pre-service teachers receive within the teacher-education programs in Algeria includes numerous aspects such as lesson planning, materials design, educational psychology, TEFL, and pedagogy. While they take in-depth training on items like lesson planning and the teaching of the macro-skills, components like assessment and evaluation remain remarkably missing from their curriculum. For observation, no module is specifically designated to assessment and evaluation along the five or four years of the training they undergo. EFL pre-service teachers are expected to graduate with adequate academic knowledge of the assessment and evaluation process; nevertheless, the reality can reveal to be contrasting. Hence, this study seeks to investigate the current situation of EFL pre-service teachers’ assessment skills which partially disclose the level of their language assessment literacy (LAL). For this, an online survey with multiple items is posted to a sample of senior EFL students at the Teacher Training College, Bouzareah (ENSB), with the purpose of collecting their reflections and analyses about different dimensions of LAL. The findings indicate that there is a glaring incongruity between the status quo of student-teachers’ assessment knowledge and the stakeholders’ aspirations from the training. This discrepancy, which is due to not receiving sufficient practicum on how to assess, demonstrates that pre-service teachers are slightly knowledgeable about items like designing different types of tests, marking, giving feedback, assessing language skills, using assessment to motivate learners, and knowing what the latter feel about assessment, as well as other critical assessment parameters.